IPTEKS TARGET DAN REALISASI PAJAK DAERAH DI DINAS PENDAPATAN DAERAH PROVINSI SULAWESI UTARA - Takahindangen, Eka A.; Pangemanan, Sifrid S. (Universitas Sam Ratulangi, 2018)
This study aims to determine the achievement of regional tax revenues and the percentage of realization of local tax revenues in the Regional Revenue Service of North Sulawesi Province in 2017-2018, which consists of Motor Vehicle Taxes, Motor Vehicle Name Transfer Fees, Surface Water Taxes, Vehicle Fuel Taxes Motorized, Cigarette Tax, Public Service Retribution, Service Service Retribution, and Specific License Licensing The results of this study indicate that the target of regional tax revenue in the North Sulawesi Provincial Revenue Service decreased in 2018 and the realization percentage of each type of regional tax revenue increased in January 2017 and November 2017. From that total it can be concluded that the increase in realization of local tax revenues in the Regional Revenue Service is able to pursue the tax deposit target in 2017.